ACIDIC LEACHING OF IRON FROM KAOJE GOETHITE ORE BY HYDROCHLORIC ACID: KINETICS MODELLING (Nigerian Journal of Technology, 2020)
Considering the recent focus of the Nigeria Government to grow and develop the nation’s economy through the solid minerals sector reform, this study has been devoted to the kinetics of a Nigerian goethite ore by hydrochloric acid leaching for improved iron and steel industries applications. This study was performed in three different phases. In the first phase, acidic leaching of iron from a goethite ore was examined and the influence of the operating variables including: HCl concentration, leaching temperature, stirring speed and particle sizes was examined experimentally. The optimum condition was found to be HCl concentration of 1.81M, temperature of 80°C, 200 rpm stirring speed and particle size 0.09 µm for iron in the range of investigated parameters. Under those conditions, the highest iron recovery was obtained to be 95.67 %. In the second phase, the dissolution kinetics of iron was evaluated by the shrinking core models. The finding reveals that diffusion through the fluid was the leaching kinetics rate controlling step of the iron. The activation energy (Ea) was found to be 14.54 kJmol-1 for iron. Equation representing the leaching kinetic of iron was achieved to be 1?2/3? - (1 ? x)2/3 = 0.7272 × e?38.29/8.314×T × t. The final stage of the experiment was carried out by characterizing the leached residues by X-ray diffractometer (XRD) and scanning electron microscopy (SEM), the result showed majorly the presence of rutile (TiO2), anglesite (PbSO4), and traces of iron-silicate face like pyrite (FeS), quartz (SiO2). http://dx.doi.org/10.4314/njt.v39i3.20